Longevidade, uma nova realidade social e humana: contribuições do fazer artístico como fortalecimento do papel social do longevo - Bóccia, Maristela de Magalhães (2009)
This thesis intends to join other efforts at showing the elderly s ability to reinvent life, and, above all, to represent a stimulus to keep on the vital drive. In order to accomplish this task, we have sought support in the speech of the elderly themselves who have participated in this research. Aiming at presenting exemples of people older than 60 years, we have collected testimonies that give value to the meaning of life, of aging, of relationships, and open opportunities for new activities. Our attempt is to discuss the impact of these opportunities on the life of the elderly, taking as a background the artistic work and its manifestations in the aging process